2020
DOI: 10.1007/s10639-020-10311-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of an evidence-based empathy mobile app in post-secondary education

Abstract: Cognitive empathy (also known as perspective-taking) is an important, teachable, skill. As part of a knowledge translation project, we identified a) interest in an evidence-based cognitive empathy mobile app and b) which faculties believe that cognitive empathy is important for their profession. Students (n = 638) and instructors/professors (n = 38) completed a university-wide survey. Participants in Education, Social Work, and the Health Sciences were among those most interested in the app. The majority of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…There are applications that allow the user to interact with their environment, use question and answers, find some element, orientate, watch instructional videos, create a portfolio, learn mathematics, play video games, and even intelligent tutoring. Likewise, research can be found that focuses on the use of some application carried out at any educational stage (Dunleavy et al, 2019;Hoplock, Lobchuk, & Lemoine, 2020;Petko et al, 2019). It is also important to note that apps tend to be used more frequently by teachers, due to their greater accessibility compared to other AI modalities, such as Big Data, which requires a higher level of literacy and involve other variables such as ethical issues (Gao, Li, & Liu, 2021).…”
Section: What Type Of Ai and Computational Science Is The Mostmentioning
confidence: 99%
“…There are applications that allow the user to interact with their environment, use question and answers, find some element, orientate, watch instructional videos, create a portfolio, learn mathematics, play video games, and even intelligent tutoring. Likewise, research can be found that focuses on the use of some application carried out at any educational stage (Dunleavy et al, 2019;Hoplock, Lobchuk, & Lemoine, 2020;Petko et al, 2019). It is also important to note that apps tend to be used more frequently by teachers, due to their greater accessibility compared to other AI modalities, such as Big Data, which requires a higher level of literacy and involve other variables such as ethical issues (Gao, Li, & Liu, 2021).…”
Section: What Type Of Ai and Computational Science Is The Mostmentioning
confidence: 99%
“…Harlick et al [15] believed that application of education APPs could significantly improve learners' interest in learning. According to Hoplock et al [16], as a means to assist teaching, applications could significantly improve learners' cognition and interest. It could be concluded from the existing research literature that APP-assisted teaching had been widely promoted and applied worldwide.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…All of these tools are accessible via a smartphone, tablet or a computer. The aim of this study is to collect and report all examples of technologies used to provide nursing education during COVID-19 [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%